Pengaruh Work Life Balance, Lingkungan Kerja Fisik Dan Lingkungan Kerja Non Fisik Terhadap Kepuasan Kerja Karyawan Pada PT. Ciomas Adisatwa - Riza Afkarina Zulfah; Budi Wahono; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
Abstract Research is aimed to determine influence work life balance, working environment and environment physical or non-physical to the satisfaction an employee at to work PT. Ciomas Adisatwa. An independent variable in this research is work life balance, environment physical labor, and workplace non-physical, and dependent variable in this research work is satisfaction. This research is kind of quantitative research using a method of a survey that was collected from a sample of people, through kuisoner. The research site in PT .Ciomas Adisatwa branches lumajang. The population in this research which is all employees of PT.Ciomas Adisatwa. A method of determining the samples for this research which is a method of sample saturated. The samples to come by as much as 68. Based on test results have been made to get a conclusion that the variable work life balance, and the physical environment have significant influence on job satisfaction, while variable non physical work environment will not affect job satisfaction. Key words: work life balance, physical, work environment non physical work environment and job satisfaction